Pattern of time utilization by multipurpose health workers male in district Sonipat, Haryana - Verma, Deepak; Majra, J. P.; Jha, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: A multipurpose health worker is the key functionary in a sub centre. They associate with the community at grass-root levels. This study explores time utilization pattern of multipurpose health workers in the multifarious domains of their activities. Methods: A time motion study conducted among health workers (HWs) male of all subcentres of district Sonipat, Haryana. Participants self‑reported their daily activities on a time measurement workbook for one month. Data were entered in Excel and analyzed using statistical package for social studies software. Results: Time utilization patterns revealed that HWs spent nearly one third (31.5%) of their time on national vector born disease control programme. Documentation constituted nearly 16.3% of their time. Others activities include maternal and child health (7.4%), service for minor ailment (6.7%), revised national tuberculosis control programme (6.7%) and meetings (4.5%). They spent 13.9% of their time on non-productive activities. The proportion of time spent on field-based activities was 63.2% and on sub center based activities was 22.9% of the total working time. A negative correlation of field-based activities was found with age, job experience and residing in joint family. Conclusions: The study reflects the time spent by HWs male in various domains of activities in relations to their job responsibilities and the multipurpose nature of their works. Some of the health programmes were ignored by HWs and were also found to be spending significant time on non-productive works.